Do direito à educação ao direito à aprendizagem : um estudo sobre culturas de intervenção pedagógica (Caxias do Sul - 1988-2013) - Lemons, Caroline Caldas (My University, 2016)
This dissertation has the objective to consider what are the concepts of right to education and right to learn that guide the narrative and the practices of the teachers in the educational system of Caxias do Sul. It aims to identify how they relate to what is envisaged in the Brazilian Constitution and in the educational policies enacted since 1988, as well to identify the kind of pedagogical intervention that are been experienced for its effectiveness. The research is justified by the growing proliferation of educational policies aimed at offering legal guarantee to the universal right to education and the incipient or invisible practical considerations on the recognition of this right in the school setting. The theoretical framework that supports the analysis and interpretation of the empirical data is grounded in theoretical and methodological contributions of authors affiliated with the History of Education and the Educational Policy in dialogue with the production of knowledge pertaining to the Philosophy of Education. Among these, helping the theoretical reflection of the concepts directly involved in the research, we point out Bobbio (1992), Reale (2002), Honneth (2003), Julia (2001), Viñao-Frago (1995), Benito (2008), Certeau (1985 e 1994), Chartier (1991), Vidal (2003, 2005 e 2010), Freire (2013) e Vigotskii (2001); on the understanding of the research context Paiva (1973), Germano (1979), Cardoso (2008), Casimiro (2011), Cury (2011), Horta (2011), Machado (2011) e Sanfelice (2011); and for guidance on methodological procedures Faria Filho (1998), Bacellar (2005), Botía (2002), Galvão (2005), Gomes e Barbosa (1999), Neto (2002), Gomes (2005) e Moraes (2007). Due to the fact that it is a qualitative approach, the research method that this dissertation welcomes adds common procedures of research in History of Education, like written narratives, coming from self applied semi-structured instruments and oral narratives, taken by the Focal Group; both ameliorated by documental and discursive textual analysis. The construction of the empirical corpus of the present research was possible by the support of the teachers of the last years of the elementary schools in Caxias do Sul. The study's findings show that even with lots of things to be done, teachers gradually advance in recognizing the right to learn subscribed on the right to education and are adopting practices that converge for a greater horizontality and social esteem. In addition, the twists of educational policies with the pedagogical ideas and teaching narratives confirm the existence of pedagogical intervention cultures, with the intention to intervene and facilitate the learning processes that take place in the formal education spaces and lengthen it temporally in favor of learning. The empirical material in dialogue with the theoretical framework of the study enabled us to identify the following categories of educational intervention: a) reproduction; b) recommendation; c) discipline; d) granting/transferring; e) emancipation.
Esta dissertação tem por objetivo geral considerar quais as concepções de direito à educação e de direito à aprendizagem perpassam as narrativas e as práticas dos professores da Rede Municipal de Ensino de Caxias do Sul, de forma a identificar como se relacionam com o que está preconizado na Constituição Brasileira e nas políticas educacionais promulgadas a partir de 1988, bem como que culturas de intervenção pedagógica são vivenciadas para a sua efetivação. O problema de pesquisa se justifica pela crescente proliferação de políticas públicas educacionais voltadas à oferta da garantia jurídica ao direito universal à educação e as incipientes ou invisíveis considerações práticas acerca do reconhecimento desse direito no âmbito escolar. O referencial teórico que sustenta a análise e a interpretação dos dados empíricos está alicerçado nas contribuições teórico-metodológicas de autores filiados à História da Educação e às Políticas Educacionais em interlocução com a produção do conhecimento atinente à Filosofia da Educação. Dentre estes, no auxílio à reflexão teórica dos conceitos diretamente envolvidos na pesquisa, se destacam Bobbio (1992), Reale (2002), Honneth (2003), Julia (2001), Viñao-Frago (1995), Benito (2008), Certeau (1985 e 1994), Chartier (1991), Vidal (2003, 2005 e 2010), Freire (2013) e Vigotskii (2001); no entendimento do contexto da pesquisa Paiva (1973), Germano (1979), Cardoso (2008), Casimiro (2011), Cury (2011), Horta (2011), Machado (2011) e Sanfelice (2011); e na orientação quanto aos procedimentos metodológicos Faria Filho (1998), Bacellar (2005), Botía (2002), Galvão (2005), Gomes e Barbosa (1999), Neto (2002), Gomes (2005) e Moraes (2007). Por se tratar de uma abordagem qualitativa, a postura de investigação que esta dissertação acolhe agrega procedimentos comuns na pesquisa em História da Educação, dentre os quais narrativas escritas, oriundas de instrumentos semiestruturados e autoaplicados e narrativas orais, advindas da prática de Grupo Focal; ambas agregadas da análise documental e da análise textual discursiva. A construção do corpus empírico da pesquisa foi possível através da colaboração dos professores do sexto ao nono ano do Ensino Fundamental da Rede Municipal de Ensino de Caxias do Sul. As conclusões do estudo apontam que mesmo havendo muito para ser feito, os professores avançam gradualmente no reconhecimento do direito à aprendizagem implícito no direito à educação e adotam práticas de mediação que convergem para uma maior horizontalidade e estima social. Além disso, os entrelaçamentos das políticas educacionais com as ideias pedagógicas e as narrativas docentes confirmam a existência de culturas de intervenção pedagógica – práticas pedagógicas com a intenção de intervir e favorecer os processos de aprendizagem que ocorrem nos espaços formais de educação e alongam-se temporalmente – em favor da aprendizagem. O material empírico, em diálogo com o referencial teórico do estudo, possibilitou identificar as seguintes categorias de intervenção pedagógica: a) de reprodução; b) de recomendação; c) de disciplina; d) de outorga/transferência; e) de emancipação.
Keywords: Educação - Caxias do Sul (RS); Educadores; Aprendizagem; Política pública; Direito à educação; Educação - História; Education - Caxias do Sul (Brazil); Educators; Learning; Public policy; Right to education; Education - History